I don't want to die poor : essays - Arceneaux, Michael (Atria Paperback, 2020)
"Ever since Oprah Winfrey told the 2007 graduating class of Howard University, 'Don't be afraid,' Michael Arceneaux has been scared to death. You should never do the opposite of what Oprah instructs you to do, but when you don't have her pocket change, how can you not be terrified of the consequences of pursuing your dreams? Michael has never shied away from discussing his struggles with debt, but in I Don't Want to Die Poor, he reveals the extent to which it has an impact on every facet of his life--how he dates; how he seeks medical care (or in some cases, is unable to); how he wrestles with the question of whether or not he should have chosen a more financially secure path; and finally, how he has dealt with his 'dream' turning into an ongoing nightmare as he realizes one bad decision could unravel all that he's earned. I Don't Want to Die Poor is an unforgettable and relatable examination about what it's like leading a life that often feels out of your control."--Amazon.com.